Anal gas evacuation and colonic microbiota in patients with flatulence: effect of diet. Issue 3 (13th June 2013) - Manichanh, Chaysavanh; Eck, Anat; Varela, Encarna; Roca, Joaquim; Clemente, José C; González, Antonio; Knights, Dan; Knight, Rob; Estrella, Sandra; Hernandez, Carlos; Guyonnet, Denis; Accarino, Anna; et al.
Abstract : Objective: To characterise the influence of diet on abdominal symptoms, anal gas evacuation, intestinal gas distribution and colonic microbiota in patients complaining of flatulence. Design: Patients complaining of flatulence (n=30) and healthy subjects (n=20) were instructed to follow their usual diet for 3 days (basal phase) and to consume a high-flatulogenic diet for another 3 days (challenge phase). Results: During basal phase, patients recorded more abdominal symptoms than healthy subjects in daily questionnaires (5.8±0.3 vs 0.4±0.2 mean discomfort/pain score, respectively; p=<0.0001) and more gas evacuations by an event marker (21.9±2.8 vs 7.4±1.0 daytime evacuations, respectively; p=0.0001), without differences in the volume of gas evacuated after a standard meal (262±22 and 265±25 mL, respectively). On flatulogenic diet, both groups recorded more abdominal symptoms (7.9±0.3 and 2.8±0.4 discomfort/pain, respectively), number of gas evacuations (44.4±5.3 and 21.7±2.9 daytime evacuations, respectively) and had more gas production (656±52 and 673±78 mL, respectively; p<0.05 vs basal diet for all). When challenged with flatulogenic diet, patients' microbiota developed instability in composition, exhibiting variations in the main phyla and reduction of microbial diversity, whereas healthy subjects' microbiota were stable. Taxa from Bacteroides fragilis or Bilophila wadsworthia correlated with number of gas evacuations or volume of gas evacuated, respectively. Conclusions: Patients complaining of flatulence have a poor tolerance of intestinal gas, which is associated with instability of the microbial ecosystem.